The "Kai Ba Lidai Shiji 开吧历代史记"; An autonomous history of the Chinese community of Batavia/Jakarta in the VOC period - Blussé, Leonard (Wacana, Journal of the Humanities of Indonesia, 2017)
This essay critically examines the Kai Ba Lidai Shiji (Annals of Batavia), a Chinese history of Batavia which was written by an anonymous Chinese author around 1794 as part of the rather large corpus of Chinese archival sources about the history of the Chinese community of Batavia/Jakarta. A short introduction about earlier authors who have dealt with the text is followed by comments on the composition, structure and historical value of this unique urban history.